Prenatal vitamin C and E supplementation in smokers is associated with reduced placental abruption and preterm birth: a secondary analysis. (17th December 2014) - Abramovici, A; Gandley, RE; Clifton, RG; Leveno, KJ; Myatt, L; Wapner, RJ; Thorp, JM; Mercer, BM; Peaceman, AM; Samuels, P; Sciscione, A; Harper, M; et al.
Abstract : Objective: Smoking and pre‐eclampsia (PE) are associated with increases in preterm birth, placental abruption and low birthweight. We evaluated the relationship between prenatal vitamin C and E (C/E) supplementation and perinatal outcomes by maternal self‐reported smoking status focusing on outcomes known to be impacted by maternal smoking. Design/Setting/Population: A secondary analysis of a multi‐centre trial of vitamin C/E supplementation starting at 9–16 weeks in low‐risk nulliparous women with singleton gestations. Methods: We examined the effect of vitamin C/E by smoking status at randomisation using the Breslow–Day test for interaction. Main outcome measures: The trial's primary outcomes were PE and a composite outcome of pregnancy‐associated hypertension (PAH) with serious adverse outcomes. Perinatal outcomes included preterm birth and abruption. Results: There were no differences in baseline characteristics within subgroups (smokers versus nonsmokers) by vitamin supplementation status. The effect of prenatal vitamin C/E on the risk of PE ( P = 0.66) or PAH composite outcome ( P = 0.86) did not differ by smoking status. Vitamin C/E was protective for placental abruption in smokers (relative risk [RR] 0.09; 95% CI 0.00–0.87], but not in nonsmokers (RR 0.92; 95% CI 0.52–1.62) ( P = 0.01), and for preterm birth in smokers (RR 0.76; 95% CI 0.58–0.99) but not in nonsmokers (RR 1.03; 95% CI 0.90–1.17) ( P = 0.046). Conclusion: In this cohort of women, smoking was not associated with a reduction in PE or the composite outcome of PAH. Vitamin C/E supplementation appears to be associated with a reduction in placental abruption and preterm birth among smokers.